Low Vitamin C Concentrations in Patients with Community-Acquired Pneumonia Resolved with Pragmatic Administration of Intravenous and Oral Vitamin C - Anitra C. Carr; Emma Vlasiuk; Masuma Zawari; Amy Scott-Thomas; Malina Storer; Michael Maze; Stephen T. Chambers (MDPI AG, 2023)
Community-acquired pneumonia (CAP) is characterized by elevated markers of inflammation and oxidative stress and depleted circulating concentrations of the antioxidant nutrient vitamin C. A feasibility trial of intravenous and oral vitamin C supplementation, matched to the timing of intravenous and oral antibiotic formulations, was carried out and changes in vitamin C status were monitored to determine whether saturating status could be achieved throughout the administration period. Patients with moderate and severe CAP (CURB-65 ≥ 2; n = 75) who were receiving intravenous antimicrobial therapy were randomized to placebo (n = 39) or intravenous vitamin C (2.5 g per 8 h; n = 36) before moving to oral vitamin C (1 g three times daily) when prescribed oral antimicrobials. Blood samples were collected at baseline and then daily whilst in the hospital. Vitamin C concentrations were determined by high-performance liquid chromatography. The inflammatory and infection biomarkers C-reactive protein and procalcitonin were elevated at baseline (158 (61, 277) mg/L and 414 (155, 1708) ng/L, respectively), and vitamin C concentrations were depleted (15 (7, 25) µmol/L). There was an inverse association between vitamin C and C-reactive protein concentrations (r = −0.312, p = 0.01). Within one day of intervention initiation, plasma vitamin C concentrations in the vitamin C group reached median concentrations of 227 (109, 422) µmol/L, and circulating concentrations remained at ≥150 µmol/L for the duration of the intervention, whilst median vitamin C concentrations in the placebo group remained low (≤35 µmol/L). There was a trend toward decreased duration of hospital stay (p = 0.07) and time to clinical stability (p = 0.08) in the vitamin C group. In conclusion, patients with moderate to severe CAP have inadequate plasma vitamin C concentrations for the duration of their hospital stay. The administration of intravenous or oral vitamin C, titrated to match the antimicrobial formulation, provided saturating plasma vitamin C concentrations whilst in the hospital. There were trends toward shorter duration of hospital stay and time to clinical stability. Thus, larger trials assessing the impact of intravenous and oral vitamin C intervention on CAP clinical outcomes are indicated.